Analyzing Coastal Community Situation of Water, Sanitation and Hygiene in Bangladesh - Khanam, Sufia; Siddik, Abubakkor; Zahid, Mohammad Abu (Fronteira: Journal of Social, Technological and Environmental Science, 2024)
There has been great success in expanding access to water, sanitation, and hygiene (WASH) services, but a large segment of the world’s poor still lacks sufficient access to such facilities. This study aimed to analyze the community situation of WASH facilities in the selected five coastal unions of Bangladesh. We surveyed all the households in the selected unions and screened functional tube wells for arsenic concentration. This study revealed that about 79.7% of households use improved water sources for drinking and other purposes while 66% of functional tube wells had arsenic contamination. In addition, about 66% of the households do not have improved sanitation systems, for instance, pit latrine with water-seal. Besides, more than 90% of households do not have hand washing facilities on premises with soap and running water within 5 meters. The community situation analysis findings may assist concern authority to improve respective WASH facilities in the study area.